Better care for children with appendicitis: implementation of antibiotic stewardship optimizes postoperative therapy - Beltz, Sebastian; Fischer, Stephanie; Huenger, Frank; Vahdad, Reza; Kalhoff, Hermann; Leutner, Andreas (GMS Hygiene and Infection Control)
Aim: Appendectomy is the most frequent emergency abdominal operation in children, who regularly present with complicated acute appendicitis and thus need targeted antibiotic therapy. While in other fields antibiotic stewardship (ABS) is becoming increasingly well established, these principles are not consistently followed in pediatric surgery. With this study, we aimed to analyze the effects of the implementation of an ABS-compliant SOP on the postoperative care of patients. Material and methods: We compared the quality of antibiotic therapy before and after the implementation of standard operating procedure (SOP) for the peri-/postoperative antibiotic treatment of appendicitis in 2020. Pediatric patients who had undergone appendectomy were evaluated based on an algorithm presenting recommended antibiotic therapy of appendicitis, according to the current literature and good clinical practice. 165 patients were evaluated before and 209 patients after the implementation of SOP. Results: The mean number of cases in which antibiotic therapy was given postoperatively was 10.5% lower (p-value 0.036) and the median quality-of-treatment score increased by 31.2% (p<0.0001) after the implementation of the SOP. The median length of antibiotic treatment in cases of advanced-stage appendicitis was 2.0 days shorter (p=0.062). The rate of oral antibiotic treatment after discharge decreased by 25.6% (p<0.0001). We observed no significant effects on the median length of hospital stay or the complication rate. Conclusion: The implementation of SOP based on the principles of ABS positively influenced the quality of treatment after pediatric appendectomy. The algorithm developed in this study may help pediatric surgeons to improve their antimicrobial assessment.